Angiopatia diabetica en paciente masculino de 87 años de edad - Bayas Chimbo, Washington Efrain (2018)
Diabetic angiopathy is a disease of the blood vessels related to the chronic course of diabetes mellitus. Diabetic angiopathy is characterized by a proliferation of the endothelium, accumulation of glycoproteins in the intimal layer and thickness of the basement membrane of capillaries and small blood vessels. This thickening causes such reduction of blood flow, especially to the extremities of the individual, that gangrene appears that requires amputation, usually of the toes or the foot itself. Occasionally amputation of the entire limb is required. Angiopathy is a very frequent complication in diabetics. The multicausal endothelial damage originates both the micro and the macroangiopathy. The dysfunction of the endothelium would be the first phase of the pathogenic sequence. There is a series of biochemical, morphological and functional markers that allow their detection in initial stages. it seems that it can also have an intervention in other vascular complications, such as nephropathy, neuropathy and macroangiopathy. The foot of the diabetic is a health problem of great importance due to its high prevalence and the sequelae it can cause. The knowledge of risk factors, the design of prevention plans and the creation of multidisciplinary teams dedicated to this pathology is the best option that we have today to improve the living conditions and the expectations of diabetic patients.